A participative method to build bridges between sustainability science and anticipatory governance at Urdaibai Biosphere Reserve (Basque Country) - Manu Monge-Ganuzas; Igor Ahedo Gurrutxaga; Iraide Álvarez Muguruza; Imanol Telleria (Oñati Socio-Legal Series, 2023)
A key-goal for governance is the translation of knowledge into planning. We recruited 125 representatives from society, technical-political and the scientific community in a participation process focused on the Urdaibai Biosphere Reserve. We analysed their testimonials by using qualitative and quantitative methods, including Computer Assisted Qualitative Contents Analysis. We validated consensuses for future management, detailing criteria for a sustainable, collaborative, and anticipatory governance. The consensuses that stood out as most important have been the following: 1. Urdaibai should work towards human well-being and prosperity. 2. Synergies between institutions and society through participation strategies are necessary. 3. It is important to have a political leadership to guide governance. We can state that the participatory process carried out allowed participants to express shared horizons on future strategies. We present the methodology of this process as well as its results since we consider that both can be useful for managers of protected areas.